A apropriação do fundo público da saúde pelas organizações sociais no município de São Paulo: o distanciamento da concepção original da Reforma Sanitária Brasileira - Correia, Daniele (2020)
The object of this research is the management of the Health Policy in the city of São Paulo, through a partnership between the government and private social organizations. This is a study on the mechanisms for transferring resources from the Municipality to Social Organizations (OS), through Management Contracts and Agreements. What motivated the research was the growing volume of resources from the public budget transferred to private organizations, under the argument of seeking greater efficiency in the management and provision of health services. In the historical-critical perspective, the research is based on works of Marxist contribution, analyzing the texts on the counter-reform of the Brazilian State in the 1990s, as well as legal-normative documents on the Unified Health System (SUS). The research scope consisted of the ten Social Organizations from the health sector that signed Management Contracts, followed by more than five hundred additive terms to manage services in the twenty-three geographical areas demarcated by the Municipal Health Department, in the modalities of primary care, urgency and emergency, specialized outpatient care and hospital care. In view of the public unavailability of the Agreements, it was not possible to measure the specificity of the performance of this management model, ensuring the focus of the study on the amount of financial resources transferred via Management Contracts and Agreements in the period from 2011 to 2019. The following references and sources of information were used: Primary Care Act; Information System on Public Health Budgets; Health Information System - DATASUS; Financial statements of the Municipality of São Paulo; Municipal Health Management Reports; Transparency Portal; articles published in journals; amongst others. In the first chapter, we carried out a retrospective characterizing the Health Policy in Brazil and the Brazilian Health Care Reform. The second chapter consists of presenting the implications of the State's counter-reform in public health, in which the implicit commodification is mainly consolidated by the OS. The analysis of the collected data is presented in the third chapter, based on which it was possible to outline the main conclusions of the research. We can measure that in the face of the crisis of capital crisis, what is being done is to necessarily bring to the State more and more forms of action that can be combined with the capital movement itself, introducing market mechanisms within the State's modus operandi. Therefore, the neoliberal logic is shaped by this scope of action, in which there is no less State, on the contrary, it is more State with greater favoring the market, in order to meet the interests of capitalist accumulation